Acupuncture combined with Chinese herbal medicine versus Chinese herbal medicine alone to improve clinical efficacy in treating endometriosis-associated pain: a systematic review and meta-analysis - Xu, Ziyi; Wang, Nanzhu; Liu, Junbo; Li, Changhui (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess the efficacy of acupuncture combined with Chinese herbal medicine (CHM) on endometriosis-associated pain.MethodsWe searched eight electronic databases (PubMed, Web of Science, EMBASE, the Cochrane Library, CNKI, Wanfang, VIP, and SinoMed) to identify randomized controlled trials (RCTs) of acupuncture combined with CHM for endometriosis-associated pain. After literature screening and data extraction, statistical analysis was done with RevMan 5.4, and the risk of bias was assessed using the Cochrane Handbook’s Risk of Bias tool.ResultsOur study included a total of 16 RCTs involving women with endometriosis-associated pain. Compared with CHM monotherapy, acupuncture combined with CHM significantly increased the clinical efficacy rate (OR = 3.75, 95% CI [2.58, 5.45], p < 0.00001) and reduced the visual analog scale (VAS) score (MD = −1.49, 95% CI [−2.43, −0.56], p < 0.0001).ConclusionThis systematic review indicates that acupuncture combined with CHM is a valuable non-hormonal option for endometriosis-related pain, outperforming CHM monotherapy in symptom relief and quality of life. It supports clinical integration, especially for patients unsuitable for hormonal therapies. However, conclusions are preliminary and require validation via large, rigorous RCTs, providing a reference for practice and future research.Systematic review registrationIdentifier, CRD420250652517, https://www.crd.york.ac.uk/PROSPERO/.